ANALISIS MINAT BACA MAHASISWA SEMESTER 1 JURUSAN EKONOMI SYARIAH - Ristu Wahyu Setiawan; Rahmawati Mulyaningtyas (Buletin Literasi Budaya Sekolah, 2021)
Reading as a means of independent learning plays an important role for students. First semester students of Islamic Economics Department as prospective Islamic-based economists have a major contribution in building the Indonesian economy. The quality of their ideas is also determined by the quality of their reading ability. Therefore, the purpose of this study was to determine reading interest, favorite types of reading, and barriers to reading interest for students majoring in Islamic Economics in first semester IAIN Tulungagung. This study uses a quantitative approach to the type of survey. Data collection techniques using a questionnaire. Descriptive analysis technique was used in this research data analysis. The subjects of this study were 113 students majoring in Islamic Economics First  semester IAIN Tulungagung. The results of this study indicate that (1) students' reading interest in Islamic Economics first semester IAIN Tulungagung tends to be at a moderate level, it can be seen that 52.2% of students like to read and 7.9% of students say they really like reading; (2) novels are the most popular reading material for Islamic economic students in first semester IAIN Tulungagung; (3) Several factors inhibiting interest in reading students majoring in islamic economic first semester IAIN Tulungagung are laziness, lack of motivation, difficulty in obtaining reading materials, and environmental factors.